Solubility and dissolutıon improvement of paramethoxycinnamic acid (pMCA) induced by cocrystal formation using caffeine as a coformer - Sulistyowaty, Melanny Ika; Fitri, Suciati; Yuliati, Ninis; Amrillah, Tahta; Che Azurahanim Che Abdullah; Setyawan, Dwi (Penerbit Universiti Kebangsaan Malaysia, 2024)
Para-methoxy cinnamic acid (pMCA) is a derivative compound of ethyl p-methoxycinnamate that could be obtained in nature. pMCA has excellent pharmacological properties. However, in their application as a drug, pMCA has poor water solubility. In this present research, we try to increase the water solubility of pMCA using the cocrystal formation (cocrystallization) strategy. Here, we use caffeine as a coformer that can interact very well with pMCA via non-covalent bonding and Van der Waals interaction to achieve cocrystal formation. The cocrystal samples were successfully synthesized using various synthesis techniques; physical mixture, solvent evaporation, and microwave radiation methods. It shows that the solubility of the samples synthesized using microwave-assisted and solvent evaporation increases about 3.30 and 3.12 times, respectively, whereas the dissolution rate profile increases 2.50 and 2.39 times, respectively, compared to pure APMS. Our findings explain the importance of the cocrystal formation strategy to enhance the solubility of active material pMCA. This strategy can also be used as a standard formulation of a new drug system with excellent solubility and dissolution which is very important for the pharmaceutical industry.